0801 Clinical Presentation, Diagnosis And Polysomnographic Findings In Children With Migraine Referred To Sleep Clinics. (27th April 2018) - Armoni Domany, K; Nahman-Averbouch, H; King, C; Dye, T; Simakajornboon, N
Abstract: Introduction: Migraine is estimated to affect 2.5–10% of the pediatric-population and has a significant economic burden. Several studies in children suggest an association between migraines and sleep disturbances, while lack of sleep is a known trigger-factor for migraine attacks. However, there is limited data regarding the clinical presentation and the polysomnographic findings for those referred for sleep evaluation. Hence, we aimed to determine the clinical presentation, diagnosis and the polysomnographic characteristics in children diagnosed with migraine who were referred to our sleep clinic. Methods: A retrospective review was performed in children with migraine evaluated in the headache clinic who were referred to the Sleep center at CCHMC between June 2007 and September 2017. Only children ≤ 18 years-old who had polysomnography (PSG) within 1 year from evaluation in the headache clinic were included. Children with major co-morbidities were excluded. Both demographic information and PSG findings were collected. Results: 256 children were included: 41% males and 71% Caucasian. The average age at the time of PSG was 12.65 ± 3.94 years-old. The average BMI was 27.87 ± 10.23 (obsese-34%). The most common presenting sleep symptoms were snoring (68%), sleep onset and sleep maintenance problems (23%), excessive daytime sleepiness (19%), restless sleep (16%), and leg movements (7%). Analysis of PSG revealed that 101 (39%) had OSA (obstructive-index, OI > 1), 33 (12.9%) had moderate- severe OSA (OI ≥ 5), 45 (16.8%) had periodic leg-movement index ≥ 5 and 7 (2.7%) had hypoventilation (ETCO2 > 50 mmHg for > 25% of the time). In addition to PSG diagnosis, other clinical diagnosis included primary-snoring (21.5%), insomnia (27.3%), restless leg syndrome/periodic limb movements disorder (RLS/PLMD) (17.5%), circadian-rhythm disorders (4.6%) and parasomnia (5%). Conclusion: Children migraine who are referred to the sleep clinic experience various types of sleep complaints. In addition to sleep disordered breathing, other sleep disorders including insomnia, RLS/PLMD, circadian-rhythm disorders and parasomnia are relatively common in this population. Additional research is needed to evaluate the effect of sleep management on clinical outcomes in the migraine population. Support (If Any): None